Ecosystemic health: considerations and insights on a kelp forest in the Strait of Messina (Italy) - Giaccone, Thalassia (O Mundo da Saúde, 2025)
The forests of Laminaria ochroleuca in the Strait of Messina and the Alboran Sea (Mediterranean Sea) are true Atlantic relict species, probably dating back to the Pliocene or earlier, that have remained isolated in these areas of the Mediterranean Sea due to the presence of chemical and physical conditions similar to those of the temperate Atlantic Ocean from which they originate. They represent a priority habitat, i.e., a natural habitat to which the European Community has assigned conservation priority. These giant kelp forests are resilient and highly relational species, establishing numerous sustainable reciprocal relationships with the biotic and abiotic environment and with the Mediterranean native coastal populations, providing various ecosystem services. The reciprocal and interconnected relationships characterizing the ecosystem services of these forests trigger a domino effect (or butterfly effect), with positive consequences for the integral health of the ecosystem in which native coastal populations are among the many beneficiary species. The well-being of a species inherently reflects the integral well-being of an ecosystem. Mediterranean native coastal populations therefore should develop a new awareness and relational skills. The objectives of this scientific contribution are to provide valuable considerations and insights on the interconnections between ecosystem services of L. ochroleuca’s forests, preliminary data, and remarks concerning participatory science and research activities carried out by researchers and divers in the Strait of Messina, as well as the integral health of the marine environment and the native Mediterranean populations living along these shores.